EVALUATION OF CARDIOVASCULAR RISK FACTORS PREVALENCE AND EFFICACY OF THEIR CORRECTION IN PHYSICIANS. ESTIMATION OF PHYSICIANS’ EXPERTISE IN UP-TO-DATE CLINICAL GUIDELINES. RESULTS OF THE “PHYSICIAN’S HEALTH AND EDUCATION” STUDY - L. Y. Drozdova; S Y. Martsevich; V. P. Voronina (Рациональная фармакотерапия в кардиологии, 2016)
Aim. To evaluate cardiovascular risk factors prevalence among physicians of therapeutic profile (cardiology , internal medicine, neurology , endocrinology etc), to estimate awareness of physicians about their own cardiovascular risk, and to simultaneously assess their expertise in up-to-date clinical guidelines. Material and methods. A total of 638 physicians working in out-patient and in-patient clinics of Moscow, Moscow region, St-Petersburg, Nizhniy Novgorod, Vladivostok, Irkutsk, Krasnoyarsk, Krasnodar and Perm were included into the study. The mean age of participants was 46 years. The mean professional experience – 20.4 years. We made an assessment of main cardiovascular risk factors, and conducted interactive inquiry , which included questions about preventive and treatment measures for cardiovascular diseases. Results. Arterial hypertension (HT) was revealed for the first time in 178 physicians, 150 physicians indicated HT in anamnesis. Only 64 physicians had target levels of blood pressure. Hypercholesterolemia rate was 45%. The prevalence of obesity and overweight were 22% and 39%, respectively. Inquiry showed that 53% of physicians primarily use clinical guidelines to choose treatment options. 76% and 88% of physicians considered it possible to achieve target levels of blood pressure and of low-density lipoprotein-cholesterol, respectively. Conclusion. Prevalence of main risk factors among physicians was similar to that in the total population; correction of those risk factors was not satisfactory. Knowledge of cardiovascular risk problems and necessity of their correction was adequate in the whole; however physicians often failed to apply their knowledge to practice.